Influence of the Martian crustal magnetic fields on the Mars-solar wind interaction and plasma transport - Li, Guokan; Lu, Haoyu; Li, Yun; Song, Yihui; Cao, Jinbin; Li, Shibang (Frontiers in Astronomy and Space Sciences, 2023)
Plasma transport process is important for the ionosphere of Mars, which controls the structure of the ionosphere above 200 km altitude as well as the location of the dayside ionopause. Meanwhile, plasma transport from the dayside ionosphere is crucial for producing the nightside ionosphere on Mars. The alteration in dayside plasma transport in the presence of crustal fields may influence the distribution of the Martian ionospheric plasma and the plasma escape in the magnetotail. This study employs a three-dimensional multispecies magnetohydrodynamic model to simulate Mars–solar wind interactions. We trace the magnetic field distribution and plasma velocity variation on the Martian dayside. The results indicate that the ion transport from low- to high-latitude areas in the south is inhibited by crustal fields, leading to the reduction in the ion number density and a thinner ionosphere near the southern terminator. Many heavy ions remain in the southern dayside ionosphere rather than moving to the nightside. In addition, the tailward flux of the planetary ions calculated by the MHD simulation is reduced by 15-50% at the southern terminator, indicating the inhibitory effect of the crustal fields on the day-to-night transport. These effects may lead to the reduction in the ion number density in the southern nightside ionosphere, and the decrease in the heavy-ion loss rate in the southern magnetotail.